2013
DOI: 10.1007/s00737-013-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the clinical effectiveness of a specialized perinatal psychiatry inpatient unit

Abstract: Women experiencing severe perinatal mental illness during pregnancy or postpartum have unique needs when psychiatric hospitalization is indicated. Although many countries have established mother-baby psychiatric units, similar facilities have not been available in the US. In 2011, the University of North Carolina at Chapel Hill inaugurated the first Perinatal Psychiatry Inpatient Unit (PPIU) in the US. We describe the unique characteristics of the patient population and report clinical outcomes guiding develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…The therapeutic needs of women with PPD also differ from those of women with depression at other times and often require a multidisciplinary approach [28,34]. For example, physicians need to consider the implications of psychotropic medications during breastfeeding and to acknowledge and treat the mother in the context of the dyadic relationship with the baby.…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…The therapeutic needs of women with PPD also differ from those of women with depression at other times and often require a multidisciplinary approach [28,34]. For example, physicians need to consider the implications of psychotropic medications during breastfeeding and to acknowledge and treat the mother in the context of the dyadic relationship with the baby.…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…Mean length of stay ranged from 6.93 days in a study in the US (Meltzer-Brody et al 2014) to 11.6 weeks in a study in Israel (Maizel et al 2005). These differences are likely to be, at least in part, due to the different nature and purpose of MBUs in different countries and regions.…”
Section: [Insert Table 2 About Here]mentioning
confidence: 99%
“…The study found that the women experienced returning home from the MBU as a significant life event, and that women did not feel they had clear enough support plans post-discharge. Meltzer-Brody et al 2014 note that additional studies need to address the transition from inpatient to community care. Howard et al (2003) use data from 1,255 mothers on the Marcé data base in 2001 to ascertain levels of continued social service supervision after discharge, noting that mothers with schizophrenia show a high risk of supervision and recommending that the whole family context should be treated.…”
Section: Secondary Theme I: Follow-up After Discharge From Mbumentioning
confidence: 99%
“…Women with severe perinatal mental illness may need to be admitted to hospital to achieve stability in a safe environment. Specialized perinatal units have been an important treatment option for women in other nations for many years,144145 and they are now being offered in the US 146147. Established across countries in Europe, psychiatric mother-baby units allow for infants to remain on the psychiatric unit with their mother 24 hours a day 144145.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Established across countries in Europe, psychiatric mother-baby units allow for infants to remain on the psychiatric unit with their mother 24 hours a day 144145. Such units have not been possible in the US owing to the healthcare system that does not support neonatal or pediatric care in the psychiatry unit; however, specialized perinatal units have been established that allow for infants to be on the unit for extended hours during the day 147. These inpatient perinatal units offer specialized care with particular attention to maternal-infant attachment.…”
Section: Emerging Treatmentsmentioning
confidence: 99%